The Gut-Liver Axis in Health and Disease: The Role of Gut Microbiota-Derived Signals in Liver Injury and Regeneration - Zheng, Zhipeng; Wang, Baohong (Frontiers in Immunology, 2021)
Diverse liver diseases undergo a similar pathophysiological process in which liver regeneration follows a liver injury. Given the important role of the gut-liver axis in health and diseases, the role of gut microbiota-derived signals in liver injury and regeneration has attracted much attention. It has been observed that the composition of gut microbiota dynamically changes in the process of liver regeneration after partial hepatectomy, and gut microbiota modulation by antibiotics or probiotics affects both liver injury and regeneration. Mechanically, through the portal vein, the liver is constantly exposed to gut microbial components and metabolites, which have immense effects on the immunity and metabolism of the host. Emerging data demonstrate that gut-derived lipopolysaccharide, gut microbiota-associated bile acids, and other bacterial metabolites, such as short-chain fatty acids and tryptophan metabolites, may play multifaceted roles in liver injury and regeneration. In this perspective, we provide an overview of the possible molecular mechanisms by which gut microbiota-derived signals modulate liver injury and regeneration, highlighting the potential roles of gut microbiota in the development of gut microbiota-based therapies to alleviate liver injury and promote liver regeneration.